Bridging the Gap: Evaluating the Effectiveness of One-Course Special Education Training in Preparing Teachers for Inclusive Classrooms in Zambia - Daniel Lupiya Mpolomoka; Joseph Mandyata; Moono Muvombo; Pelekelo Kabundula; Mohammad, A. Beirat (Journal of Early Childhood Development and Education, 2025)
Background of Study: Inclusive education is a growing priority in Zambia, yet many teacher education programs rely on a single special education course to prepare teachers for inclusive classrooms. This raises concerns about the sufficiency of such training in equipping educators with the necessary competencies. Aims and Scope of Paper: This study aims to critically evaluate the effectiveness of a one-course special education module in preparing both pre-service and in-service teachers for inclusive classroom settings in Zambia. It explores the perceptions and lived experiences of teachers undergoing this training. Methods: Guided by Vygotsky’s Sociocultural Theory and a pragmatic philosophical stance, the study adopted an interpretive phenomenological design with a qualitative approach. Data were collected through semi-structured interviews and focus group discussions with 10 student teachers and 5 practicing teachers, selected purposively. Thematic analysis was used to analyze the data. Results: Findings reveal that while the course provides basic conceptual understanding of inclusive education, it falls short in areas such as practical application, mentorship, and continuous professional development. Participants expressed a lack of preparedness in handling the complexities of inclusive classrooms. Conclusion: The study concludes that a single-course model is inadequate for preparing teachers for inclusive education. It recommends comprehensive reform in teacher education programs, including longitudinal training, integration of assistive technology, and structured mentorship to enhance teacher readiness and align training with inclusive education goals.